Altered frontal and insular functional connectivity as pivotal mechanisms for apathy in Alzheimer's disease. (October 2019) - Jones, Sarah A.; De Marco, Matteo; Manca, Riccardo; Bell, Simon M.; Blackburn, Daniel J.; Wilkinson, Iain D.; Soininen, Hilkka; Venneri, Annalena
Abstract: Background: Apathy is a common and early symptom in Alzheimer's disease (AD) and is linked to poorer prognosis. Theoretical interpretations of apathy implicate alterations of connections amongst fronto-striatal and limbic regions. Objective: To test the association between presence of apathy and patterns of brain functional connectivity in patients with clinically-established AD. Methods: Seventy AD patients were included. Thirty-five patients experienced apathy as defined by the screening question of the Neuropsychiatric Inventory, and thirty-five did not. All patients agreed to undergo an MRI protocol inclusive of resting-state acquisitions. The hemodynamic-dependent signal was extracted bilaterally from five regions of interest: ventromedial prefrontal cortices, anterior cingulate cortices, dorsolateral prefrontal cortices, insulae and amygdalae. t tests were run to compare connectivity maps of apathetic and non-apathetic patients. Age, education, Mini Mental State Examination score, gray matter volumes and gray matter fractions served as covariates. Results: At a p FWE < .05 threshold, apathetic patients had reduced connectivity between the left insula and right superior parietal cortex. Apathetic patients had also increased connectivity between the right dorsolateral prefrontal seed and the right superior parietal cortex. Patients with apathy were significantly more likely to experience other psychiatric symptoms. Conclusion: Our findings support a role of frontal and insular connections in coordinating value-based decisions in AD. Both down-regulation and maladaptive up-regulation mechanisms appear to be at play in these regions.